High-TC superconductivity in Cs3C60 compounds governed by local Cs–C60 Coulomb interactions. (2nd March 2017) - Harshman, Dale R; Fiory, Anthony T
Abstract: Unique among alkali-doped A 3 C60 fullerene compounds, the A15 and fcc forms of Cs3 C60 exhibit superconducting states varying under hydrostatic pressure with highest transition temperatures at T C meas   =  38.3 and 35.2 K, respectively. Herein it is argued that these two compounds under pressure represent the optimal materials of the A 3 C60 family, and that the C60 -associated superconductivity is mediated through Coulombic interactions with charges on the alkalis. A derivation of the interlayer Coulombic pairing model of high- T C superconductivity employing non-planar geometry is introduced, generalizing the picture of two interacting layers to an interaction between charge reservoirs located on the C60 and alkali ions. The optimal transition temperature follows the algebraic expression, T C0   =  (12.474 nm 2 K)/ ℓζ, where ℓ relates to the mean spacing between interacting surface charges on the C60 and ζ is the average radial distance between the C60 surface and the neighboring Cs ions. Values of T C0 for the measured cation stoichiometries of Cs3− x C60 with x   ≈  0 are found to be 38.19 and 36.88 K for the A15 and fcc forms, respectively, with the dichotomy in transition temperature reflecting the larger ζ and structural disorder in the fcc form. In the A15 form, modeled interacting charges and Coulomb potential e 2 / ζ are shown to agree quantitatively with findings from nuclear-spin relaxation and mid-infrared optical conductivity. In the fcc form, suppression of T C meas below T C0 is ascribed to native structural disorder. Phononic effects in conjunction with Coulombic pairing are discussed.